2019
DOI: 10.1371/journal.pntd.0007227
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamomum cassia exhibits antileishmanial activity against Leishmania donovani infection in vitro and in vivo

Abstract: Background There is a pressing need for drug discovery against visceral leishmaniasis, a life-threatening protozoal infection, as the available chemotherapy is antiquated and not bereft of side effects. Plants as alternate drug resources has rewarded mankind in the past and aimed in this direction, we investigated the antileishmanial potential of Cinnamomum cassia . Methodology Dichloromethane, ethanolic and aqueous fractions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 77 publications
4
14
0
Order By: Relevance
“…The antimicrobial and antiparasitic activities are also in agreement with previous reports, where oregano and cinnamon EO and their major components are the most effective antimicrobials [5,29]. However, there are differences in an EO's effect for each microbial strain tested, showing that the effect can vary depending on the microorganism, and there are even variations among strains of a similar microbial species [15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The antimicrobial and antiparasitic activities are also in agreement with previous reports, where oregano and cinnamon EO and their major components are the most effective antimicrobials [5,29]. However, there are differences in an EO's effect for each microbial strain tested, showing that the effect can vary depending on the microorganism, and there are even variations among strains of a similar microbial species [15].…”
Section: Discussionsupporting
confidence: 90%
“…The determination of cell death markers by flow cytometry can provide information on the timeline of the events presented in the interaction of protozoans with EO or their major components. Flow cytometry analysis can suggest if the cellular damage to protozoans results from a necrotic or an apoptotic effect [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EBC (50 and 100 mg/kg) showed significant protection against L. donovani infected mice and hamsters, the in vivo protection achieved was 80.91% (liver) and 82.92% (spleen) in mice and 75.61% (liver) and 78.93% (spleen) in hamsters. The results showed that Cinnamomi Cortex had direct antileishmanial activity and non-toxicity in vitro and in vivo [107].…”
Section: Pharmacologymentioning
confidence: 99%
“…The in vivo activity of LASSBio-1386 was investigated using BALB/c mice, which are highly susceptible to Leishmania infection (Afrin et al, 2019). Treatment by topical route with LASSBio-1386 decreased the size of the lesion and the parasite load.…”
Section: Discussionmentioning
confidence: 99%